PENGAJUAN PUTUSAN BEBAS PADA TINGKAT BANDING DAN KASASI - Giska Ari Kusumadewi, Putu; Satyayudha Dananjaya, Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
Acquittal occurs if the evidence at the trial was not sufficient enough to prove guilt of theaccused as well as the lack of judge confidence. Acquittal divided into pure acquittal and impureacquittal. Pure acquittal is a final decision that means closing the possibility of an appeal or acassation against the case, while impure acquittal might be appealed or bring into cassation to thespecific requirements. The purpose of this study is to determine whether the acquittal might beappealed or cassation effort. This study used a normative method that utilizes primary andsecondary data sources.
Keywords: Acquittal, Impure Acquittal, Appealed, Cassation